Perbandingan Rasio Keuangan Bank Muamalat, BTN Syariah dan Bank Syariah Indonesia Periode 2017-2023 - Retno Farika; Faizin, Moh. (Falahiya: Journal of Islamic Banking and Finance, 2025)
Introduction: Ratio explains the relationship between one amount and another amount. An analyst can gain insight into a company's financial situation and its good and bad aspects by using ratios as an analytical tool. The purpose of financial ratio analysis is to help managers understand what a business should do given its limited financial data. This research aims to compare the financial ratios of BSI, BTN Syariah and Bank Muamalat Indonesia in terms of NPF, ROA and FDR. Research Methods: This research is included in Quantitative research using comparative analysis. The population in this study were financial reports from BSI, BTN Syariah and BMI with 84 financial report samples. Analysis of this research data used the One Way Anova test with the help of the IBM SPSS version 26 program. Results: From this research, the results obtained: there is no difference in the financial ratios of BSI, BTNS and BMI on the NPF variable. The financial ratios in terms of BSI ROA do not have a significant difference with the BTNS ROA value, and the BSI and BTNS ROA values ​​have a significant difference with the BMI ROA value. Conclusion: There are differences in the financial ratios of BSI, BTNS and BMI in terms of FDR